CLINICAL THINKING AND MEDICAL PROFESSION - N. I. Volkova; P. P. Slavny (Медицинский вестник Юга России, 2015)
Clinical thinking - the multiple-factor, volume concept consisting in generation of special type of thought process, formed on the knowledge base of practical work. The steady interest based on real ideas of a certain field of activity, approaches the person to his highest requirement – need for self-updating. Psychological testing instead of interview has to be one of conditions of selection of entrants in medical schools. It is necessary to select shots of a certain psychological status for which individually steady requirement – need for achievement is characteristic. It explains persistence of the doctor during work to receive high performance, and not to pay attention to temporary failures.